A Multiyear Constraint on Ammonia Emissions and Deposition Within the US Corn Belt. Issue 6 (22nd March 2021) - Hu, Cheng; Griffis, Timothy J.; Frie, Alexander; Baker, John M.; Wood, Jeffrey D.; Millet, Dylan B.; Yu, Zhongjie; Yu, Xueying; Czarnetzki, Alan C.
Abstract: The US Corn Belt is a global hotspot of atmospheric ammonia (NH3 ), a gas known to adversely impact the environment and human health. We combine hourly tall tower (100 m) measurements and bi‐weekly, spatially distributed, ground‐based observations from the Ammonia Monitoring Network with the US National Emissions Inventory (NEI) and WRF‐Chem simulations to constrain NH3 emissions from April to September 2017–2019. We show that: (1) NH3 emissions peaked from May to July and were 1.6–1.7 times the annual NEI average; (2) average growing season NH3 emissions from agricultural lands were remarkably similar across years (3.27–3.64 nmol m −2 s −1 ), yet showed substantial episodic variability driven by meteorology and land management; (3) dry deposition was 40% of gross emissions from agricultural lands and exceeded 100% of gross emissions in natural lands. Our findings provide an important benchmark for evaluating future NH3 emissions and mitigation efforts. Key Points: Rare multiyear tall tower and ground‐based ammonia measurements were combined with WRF‐Chem to constrain emissions from the US Corn Belt Monthly ammonia emissions peaked in May through July and were 1.6–1.7 times the annual NEI average Episodic low WRF‐Chem bias versus tall tower observations underscore the importance of weather and land management as emission drivers